2008
DOI: 10.1002/ijc.24024
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor ß1 induces apoptosis by suppressing FLICE‐like inhibitory protein in DU145 prostate epithelial cells

Abstract: Transforming growth factor ß (TGFß) is a paracrine mediator of prostate epithelial cell apoptosis. In rodents, castration induces production of TGFb by stromal cells, which leads to apoptosis of epithelial cells. To identify potential mediators of this cell death pathway, we developed a model using DU145 cells, a tumorigenic human prostate epithelial cell line. We discovered that at low density, in low mitogen media, DU145 cells apoptose when treated with TGFb1. Prior to the onset of death, TGFb1 treatment dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…This complicated our view on how TGFβ and Pak1 may be associated in the promotion of prostate cancer cell invasion. Our results indicated that TGFβ1 overexpression in PC3 prostate tumor xenografts induced apoptosis mainly through the activation of stress-activated p38-MAPK pathway, thus confirming the predominant role of TGFβ1 as a tumor suppressor (Al-Azayzih et al, 2012; Nastiuk et al, 2008; Pu et al, 2009; Song et al, 2010; Yoo et al, 2009). Surprisingly, TGFβ1 overexpression resulted in significantly increased active Rac1 and phosphorylated Pak1/2 accompanied by increased expression of a mesenchymal markers Snail and N-Cadherin.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This complicated our view on how TGFβ and Pak1 may be associated in the promotion of prostate cancer cell invasion. Our results indicated that TGFβ1 overexpression in PC3 prostate tumor xenografts induced apoptosis mainly through the activation of stress-activated p38-MAPK pathway, thus confirming the predominant role of TGFβ1 as a tumor suppressor (Al-Azayzih et al, 2012; Nastiuk et al, 2008; Pu et al, 2009; Song et al, 2010; Yoo et al, 2009). Surprisingly, TGFβ1 overexpression resulted in significantly increased active Rac1 and phosphorylated Pak1/2 accompanied by increased expression of a mesenchymal markers Snail and N-Cadherin.…”
Section: Discussionsupporting
confidence: 74%
“…Since TGFβ is a well-known tumor suppressor in prostate cancer cells (Al-Azayzih et al, 2012; Edlund et al, 2003; Hayes et al, 2001; Yoo et al, 2009), we assumed that increased TGFβ expression due to Pak1 inhibition may have an effect on the inhibition of tumor growth in addition to the effect of Pak1 inhibition on cytoskeletal remodeling in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both apoptotic and EMT responses to TGF-β treatment in PC3 and DU145 prostate cancer cells has been observed in separate studies [49][50][51], which suggests that a concomitant apoptosis and EMT may also occur in response to TGF-β in these cells. In the concomitant apoptosis and EMT, accumulating data have shown that the extent of both events can be modulated by either pro-survival and/ or pro-apoptotic factors.…”
Section: Tgf-β-induced Concomitant Apoptosis and Emtmentioning
confidence: 86%
“…TGF-β1-induced apoptosis has been observed in a number of nonrenal cell lines including prostate cancer cells, gastric caner cells, hepatocytes, and uterine epithelial cells. 4548 Mice treated with an anti-TGF-β1 neutralizing antibody had reduced tubule apoptosis and nephron loss in a model of renal injury created by unilateral ureteral obstruction indicating a role for TGF-β1 in apoptosis. 49 More evidence for TGF-β1 involvement was demonstrated in angiotensin II induced apoptosis of cultured proximal tubular epithelial cells.…”
Section: Tgf-β and The Kidneymentioning
confidence: 99%